THE ROLE OF CLASSROOM TEACHER AND SCHOOL CULTURE IN THE SPIRIT OF NATIONAL INVESTMENT - Mul Yati; Irawan Suntoro; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2012)
The purpose of this study is a first grade teacher identifies the role of the national spirit in the planting of elementary school students saving Earth Udik East Lampung District School Year 2012/2013, explain the role of school culture in the planting of the national spirit elementary school students saving Earth Udik Academic Year 2012/2013. Method used correlational. This research is a study population with the number of respondents 6 teachers. Data analyses used Chi Quadrate. The results showed that: (1) the class teacher has not been instrumental in planting the spirit of nationalism. (2) culture has not been instrumental in planting the spirit of nationalism. Key Words: Master Class, School Culture, The Spirit Of Nationality